Pengaruh Pajak Kendaraan Bermotor Terhadap Penerimaan Pajak Daerah Pada BPRD Provinsi DKI Jakarta - Dedi Suharyadi; Rini Martiwi; Eulin Karlina (Universitas Bina Sarana Informatika, 2019)
Motor vehicle tax is still the second largest contributor in regional tax revenue after the Transfer of Motor Vehicle Title Fee (BBN-KB) in the DKI Jakarta area. Therefore PKB needs to be optimized because of its large contribution to tax revenue, given the increasingly rapid growth of motorized vehicles in DKI Jakarta. The purpose of this study was to determine how the influence of Motor Vehicle Tax Against Regional Tax Revenue in BPRD DKI Jakarta. The method used in this study is a quantitative method with a simple linear regression statistical analysis. The results showed that there was a significant influence between motor vehicle tax with local tax revenue of 0,933 or 93,3% while the remaining 0,067 or 6,7% explained other independent variables not included in this study. Based on the correlation test shows a very strong relationship between motor vehicle tax with local taxes of 0,966. Positive correlation shows that if the motor vehicle tax revenue gets bigger then the local tax revenue will increase. The formed regression equation is Ŷ = 2,266 + 0,841X1 illustrated that Constants (a) = 2,266 show constant values, where if the variable Motor Vehicle Tax (X1) equals zero (0) then the Local Tax (Ŷ) = 2,266. Motor Vehicle Tax (X1) regression coefficient of 0,841 means that if other independent variables have a fixed value and the Motor Vehicle Tax has increased by 1% then the Regional Tax (Y) will have an increase of 0,841. Keywords: Motor Vehicle Tax, Local Tax.